Bilingualism in Colombia Higher Education - Sandra Liliana Martínez Rincón (Enletawa Journal, 2017)
This theme review describes aspects related to bilingualism and its incidence in higher education. Specifically, the author shows a brief overview of what bilingualism means; what the National Bilingual Program started in 2004 and its evolution into Colombia, very well for 2015 entail in terms of their impact on both teaching and learning; and the importance for the Ministry to modify certain aspects regarding bilingualism in education in our country.